Penerapan Model Pembelajaran Matematika Realistik untuk Meningkatkan Motivasi Belajar Matematika - Abidin, Zainal (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2022)
Based on the results of initial observations, it was found that students' motivation to learn mathematics was still lacking in terms of solving math problems. For this reason, the authors apply a realistic mathematics learning model in describing the process of applying a realistic mathematics learning model to increase students' motivation to learn mathematics. The type of research used in this research is Classroom Action Research (CAR). The results of this study were seen from the increase in students' motivation to learn mathematics in each cycle. The results of student learning motivation at the end of the lesson were 71.7% in the first cycle and 80.3% in the second cycle. Based on the results of the study, it can be concluded that the application of a realistic mathematics learning model can increase students' motivation to learn mathematics.